The greatest era of the UK pop music industry: An efficiency perspective - Hon, Lee (Popular Music History, 2015)
As one of the biggest nations in the world in terms of music industry revenue, the UK prides itself as an industry leader in the sector, both commercially and artistically. Ever since the inception of the UK pop charts back in 1952, the country has seen several highs and lows although the sector remains as vibrant and innovative as ever. The height of the industry’s achievements undoubtedly came in the early 1960s and 1980s, two high points in the UK music industry which saw UK artistes scaling the charts all over the world, most notably conquering even the US pop charts thus leading to the term British invasion. Employing DEA methodology, this paper compares the achievements of five decades in UK pop history and found the 1980s to be the most efficient decade in terms of musical achievements. In addition, 1981 was the year which was benchmarked the most hence earning the “most efficient year” tag in UK music history. From the results, the second British invasion, an era which was spearheaded by the New Romantics movement is the best era in British music folklore, surpassing even the first invasion, which was then led by the legendary band, The Beatles.